A high-efficiency flame-retardant heat-insulating material for building and preparation method thereof
By using a combination of phosphorus-containing modified polyol and other flame retardants in the hard foam polyurethane insulation material, the problem of flammability of the material is solved, and efficient flame retardant and excellent insulation properties are achieved.
Patent Information
- Application Number
- CN202410625251.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-05-20
AI Technical Summary
Because the hard foam polyurethane insulation material is highly flammable, the oxygen index is low when the flame retardant treatment is not done, resulting in a high fire risk, making it difficult to meet the A-level non-combustible requirements when the building height is greater than 50 meters.
The modified polyol containing phosphorus elements is used to combine it with N-type flame retardant, modified expandable graphite, and condensed phase flame retardant. The phosphorus elements are introduced through the transesterification reaction to uniformly disperse the flame retardant characteristic elements, and jointly improve the flame retardant performance of the material.
It realizes efficient flame retardant of polyurethane materials, achieves flame retardant effect above level A2, and at the same time improves the insulation properties and mechanical strength of the material, reducing the overall density and risk of shedding.
Smart Images

Figure BDA0004848393050000041 
Figure BDA0004848393050000121 
Figure BDA0004848393050000122
Abstract
Description
Technical Field
[0001] The present application relates to a high-efficiency flame-retardant heat-insulating material for construction and a preparation method thereof, belonging to the technical field of flame-retardant building materials. Background Art
[0002] Rigid polyurethane foam insulation material is a polymer with repeating structural units of urethane segments made by the reaction of isocyanate and polyol. As a high molecular thermosetting thermal insulation material, it has the best thermal insulation performance among all organic thermal insulation materials for exterior walls. Rigid polyurethane foam insulation material has been used in the construction field for many years due to its good thermal insulation performance and excellent waterproof performance. It is widely used in the fields of exterior wall insulation, roof insulation, etc.
[0003] Polyurethane generally does not decompose below 202°C. The ignition temperature of polyurethane foam measured by ASTM D1929 is 310°C for forced ignition temperature and 415°C for spontaneous combustion temperature. Polyurethane foam is essentially a highly flammable material, and its oxygen index is only 16.5% when it is not flame retardant. Thermosetting materials usually decompose flammable gases when heated, and form a carbonized layer after being exposed to fire. The products of thermal decomposition and combustion are mainly hydrogen cyanide, CO, isocyanate, etc. These fumes and gases not only hinder the rescue of trapped people, but also have a certain negative effect on surrounding buildings. The fire hazard of rigid polyurethane foam has long attracted attention at home and abroad, so it is urgent to improve the flame retardancy of rigid polyurethane foam.
[0004] The national mandatory standard stipulates that when the building height is greater than 50 meters, the combustion performance of the thermal insulation material must reach Class A non-combustible. At the same time, with the proposal of the "carbon peak and carbon neutrality" goals, the state and local governments continue to introduce building energy-saving policies. Therefore, the market needs Class A flame-retardant materials with high thermal insulation performance. In order to improve the flame retardant properties of polyurethane rigid foam materials, polyurethane rigid foam materials used in the construction field need to be flame-retardant treated.
[0005] There are two types of flame retardants commonly used in polyurethane polymers: additive flame retardants and reactive flame retardants. Additive flame retardants refer to physically adding a large amount of inorganic fillers to improve the flame retardant properties of the material, but there are obvious problems: First, the overall density of the product is too high, and it is easy to fall off when used on the actual building exterior wall; second, the high filling ratio of inorganic materials will cause the inorganic fillers to settle rapidly during the foaming process, resulting in uneven upper and lower layers, which is not conducive to improving the thermal insulation performance of the product; third, the filling ratio of inorganic materials is too high. During the production process, it is difficult to achieve uniform mixing of high-proportion inorganic fillers with polyurethane foam, and the homogeneous properties of the material are difficult to ensure. At the same time, the mechanical properties are usually greatly affected. Reactive flame retardants can solve the above problems of additive flame retardants to a certain extent. However, the amount of reactive flame retardants usually added is not too much. If too much is added, it will affect the foaming performance of the polyurethane material. Therefore, when the amount added is small, it will cause the problem of uneven flame retardancy. Summary of the invention
[0006] In order to solve the above problems, a high-efficiency flame-retardant thermal insulation material for construction is provided, which adopts a modified polyol containing phosphorus element to react, so as to achieve uniform dispersion of phosphorus flame retardant elements and increase the proportion of effective characteristic flame retardant elements, so that the flame retardant characteristic elements can uniformly play a flame retardant role, and the modified polyol is combined with N-series flame retardant, modified expandable graphite and condensed phase flame retardant to synergistically improve the flame retardancy of the material, and can also improve the mechanical strength and thermal insulation performance of polyurethane under the above-mentioned material proportion.
[0007] According to one aspect of the present application, there is provided a high-efficiency flame-retardant heat-insulating material for construction, which comprises, by weight:
[0008] 110-120 parts of modified polyol, 8-10 parts of diol, 120-140 parts of isocyanate, 10-20 parts of N-series flame retardant, 5-20 parts of modified expandable graphite, 150-280 parts of condensed phase flame retardant, 13-15 parts of blowing agent, 0.3-0.5 parts of first catalyst, 2.5-3.0 parts of uniform foaming agent, 1 part of water;
[0009] The modified polyol contains phosphorus element.
[0010] The present application adopts modified polyols with phosphorus elements and isocyanates to react to generate polyurethane materials, which can introduce flame-retardant phosphorus elements into the cross-linked molecular chains of polyurethane, so that the polyurethane itself has flame retardancy, thereby improving the flame retardancy uniformity of the material. In addition, N-series flame retardants, modified expandable graphite, and condensed phase flame retardants are added to the material to cooperate with each other, which can synergistically improve the flame retardancy of the material. At the same time, since the polyurethane molecular chain contains flame retardant elements, the amount of expandable graphite and condensed phase flame retardant can be greatly reduced, so that the overall density of the material is reduced, which is convenient for large-scale transportation and use, and reduces the possibility of wall shedding.
[0011] Optionally, the modified polyol is obtained by modifying the polyol with a liquid phosphorus-based flame retardant, and the specific preparation method is:
[0012] After mixing the polyol and the liquid phosphorus flame retardant in a weight ratio of 8-9:1, adding a second catalyst and reacting at 120-150° C. for 12-15 hours to obtain a modified polyol.
[0013] The polyol and the phosphorus-based flame retardant undergo an ester exchange reaction, which can introduce phosphorus into the polyol to obtain a modified polyol. The above weight ratio can increase the phosphorus content in the modified polyol, thereby increasing the proportion of effective flame-retardant phosphorus in the polyurethane molecular chain, thereby further improving the flame retardant performance.
[0014] Optionally, the polyol is selected from polyether polyol and polyester polyol, and the hydroxyl value of the polyol is 350-650 mg KOH / g.
[0015] Preferably, the polyether polyol is selected from polyether triol or polyether tetraol; the polyester polyol is selected from polycaprolactone polyol, polycarbonate polyol or polyacrylate polyol.
[0016] The second catalyst is selected from dibutyltin oxide.
[0017] Optionally, the phosphorus-based flame retardant is selected from at least one of dimethyl methylphosphonate, triphenyl phosphate, tributyl phosphate, and tris(β-chloroethyl) phosphate.
[0018] Optionally, the phosphorus-based flame retardant is selected from dimethyl methylphosphonate and tris(β-chloroethyl) phosphate in a weight ratio of 1:4.
[0019] It has been verified that the presence of the above two phosphorus-based flame retardants can improve the reaction efficiency of the phosphorus-based flame retardants and polyols, increase the proportion of phosphorus elements in the modified polyols, and thus achieve better flame retardant effects. Halogen elements are also introduced to improve the flame retardant properties of the material without reducing the thermal insulation and mechanical properties of the material.
[0020] Optionally, the diol is prepared from N,N-bis(hydroxymethyl)-urea, and the specific preparation method is:
[0021] S1: dissolving N,N-bis(hydroxymethyl)-urea in a solvent, adding formic acid and formaldehyde at room temperature, wherein the molar ratio of N,N-bis(hydroxymethyl)-urea, formic acid and formaldehyde is 1:1:1, then heating to 70-80°C for reaction for 9-12h, then adjusting the pH to 10-11, extracting and drying to obtain an intermediate;
[0022] S2: dissolving the intermediate in ethanol, adding a small amount of citric acid and disodium ethylenediaminetetraacetate, heating to 60-70°C, adding hydrogen peroxide, wherein the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)-urea is 1:1, reacting for at least 4 hours, distilling and purifying to obtain the diol.
[0023] The diol itself can be used as a chain extender to extend the molecular chain length of the polyurethane material, thereby adjusting the crosslinking degree of the polyurethane material to adjust the mechanical properties, foaming uniformity and thermal insulation of the polyurethane material. The present application further adopts a homemade diol, which not only has two hydroxyl groups that can participate in the reaction of the polyurethane, but also has two amine oxide groups through the reaction of steps S1 and S2. First, it can enhance the flame retardant effect of the polyurethane molecular chain; second, it can improve the compatibility with N-series flame retardants and promote the uniform dispersion of N-series flame retardants; third, it can suppress the amount of smoke generated by material combustion and reduce the generation of combustion gases.
[0024] The other two amine oxide groups are both connected to the carbon-oxygen double bond. It has been verified that the carbon-oxygen double bond can promote the above-mentioned effect of the amine oxide, and the closer the carbon-oxygen double bond is to the amine oxide group, the more obvious the promotion effect. Therefore, the carbon-oxygen double bond contained in the diol in the present application is directly connected to the two amine oxide groups, which can optimize the above-mentioned effect of the amine oxide.
[0025]
[0026] Optionally, the added amount of citric acid accounts for 2% of the weight of N,N-bis(hydroxymethyl)-urea, and the added amount of disodium ethylenediaminetetraacetate accounts for 5% of the weight of N,N-bis(hydroxymethyl)-urea.
[0027] Preferably, the solvent is a mixed solvent of water and ethanol in a weight ratio of 2-3:1.
[0028] Optionally, the condensed phase flame retardant is selected from at least one of Sb2O3, Mg(OH)2, Al(OH)3, B2O6Zn3, silicon oxide, aluminum oxide, aluminum silicate, calcium silicate, clay powder, feldspar powder, talc powder, copper oxide, copper hydroxide, cobalt hydroxide, chromium hydroxide, and zinc hydroxide.
[0029] Optionally, the particle size of the condensed phase flame retardant is less than 10 μm;
[0030] The modified expandable graphite has a particle size of 0.5-10 μm and an expansion coefficient of 250-290 ml / g.
[0031] Optionally, the modification method of the modified expandable graphite is:
[0032] S10: Phosphoric acid and urea are mixed in a molar ratio of (0.5-1):1, and reacted at 80-100° C. to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100° C. to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240° C. and 10-45 KPa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A;
[0033] S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups;
[0034] S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone;
[0035] S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.
[0036] In the preparation method, the intermediate microspheres A obtained in step S10 contain ammonium polyphosphate between the graphite layers, which can improve the adhesion between the expandable graphite, thereby improving the flame retardant effect of the expandable graphite. In step S20, N-aminoethyl-3-aminopropyltriethoxysilane is used to react with the intermediate microspheres A to obtain the intermediate microspheres B. Firstly, the compatibility of the intermediate microspheres B with the polyurethane substrate can be improved, so that the expandable graphite and the matrix form a uniform and stable state, and the sedimentation and agglomeration of the expandable graphite are avoided, thereby improving the performance uniformity of the polymer matrix and the flame retardant uniformity of the expandable graphite to the matrix; secondly, the intermediate microspheres B contain NH and NH2 groups, which can not only absorb toxic gases and reduce the combustion hazard, but also participate in the reaction of isocyanate to form polyurethane, form a chemical bond with the polyurethane matrix, and improve the bonding force between the expandable graphite and the matrix, so that the flame retardant carbon layer is tightly combined with the matrix, and the protection of the matrix is improved. In step S30, the intermediate microspheres C can also be obtained by reacting with the monomer A formaldehyde compound. Due to the presence of monomer A, the intermediate microspheres C prepared in step S30 can introduce functional groups such as benzene rings, carbonyl groups, ester groups, and amino groups into expandable graphite. The benzene rings can strengthen the matrix and improve the mechanical properties of the matrix. The carbonyl groups and ester groups can further increase the compatibility with the polyurethane matrix. The amino groups can further increase the number of binding sites with the polyurethane matrix and increase the adsorption of toxic gases. Since the monomers A in step S30 all contain double bonds, 3-mercaptopropyltriethoxysilane is used in step S40 to react with the double bonds to obtain silane-terminated modified expandable graphite, which can further improve the dispersibility and stability of expandable graphite in the matrix, and improve the adhesion between expandable graphites, so that the strength and density of the flame-retardant carbon layer are improved, so that the toxic gases are adsorbed and effectively blocked, reducing the harm of toxic gases to the human body.
[0037] The intermediate microspheres A obtained in the above step S10 allow ammonium polyphosphate to be contained between the graphite layers, which not only improves the bonding force between the expandable graphites and increases the strength of the flame-retardant carbon layer, but also can simultaneously improve the flame-retardant properties of the expandable graphite because the ammonium polyphosphate itself is also flame-retardant; in steps S20-S40, the surface of the expandable graphite contains modified molecular chains, which can firstly achieve the adsorption of toxic gases; secondly, improve the compatibility of the expandable graphite with the matrix, improve the dispersion uniformity of the expandable graphite, avoid the sedimentation or agglomeration of the expandable graphite, and also improve the performance uniformity of the polyurethane composite material; thirdly, it can be chemically combined with the polyurethane matrix, so that the flame-retardant carbon layer is tightly combined with the matrix, and the toxic gas is effectively blocked, and the compactness, uniformity and mechanical strength of the flame-retardant carbon layer can be improved, and it can resist the impact of open flames or heat convection.
[0038] The modified expandable graphite prepared by the above method can be more evenly dispersed, so when used as a flame retardant, the usage amount can be effectively reduced, thereby reducing the density of the material, and also avoiding the problem of falling off due to excessive mass when used as a building exterior wall.
[0039] Optionally, in step S10, the expandable graphite accounts for 5-30% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate.
[0040] In the above step S10, the intermediate microspheres A are obtained by a homogenizing emulsification process, which can solve the problem of difficult dispersion of expandable graphite and ammonium polyphosphate emulsion. Under the high shear force of the homogenizing emulsifier, many small droplets are formed inside the emulsion, and the microstructure of the expandable graphite particles wrapped by the ammonium polyphosphate emulsion is realized. During the polymerization process, the expandable graphite particles can be evenly dispersed, thereby improving the modification effect of ammonium polyphosphate on the expandable graphite.
[0041] Since the expandable graphite contains ammonium polyphosphate between the layers, the ammonium polyphosphate decomposes into ammonia and polyphosphoric acid when heated. The ammonia can dilute the oxygen concentration, and the polyphosphoric acid has good thermal stability. The expandable graphite expands rapidly after heating, which can effectively isolate the oxygen required for combustion. At the same time, the interior has a porous property, which absorbs the combustion smoke and reduces the possibility of re-combustion. It can also effectively isolate the combustion oxygen and improve the flame retardant properties of the material.
[0042] Optionally, in step S20, the weight ratio of the intermediate microsphere A to N-aminoethyl-3-aminopropyltriethoxysilane is 1:(1-2);
[0043] The heating reaction time in step S20 is 8-10 hours.
[0044] The surface of expandable graphite contains a large number of hydroxyl groups. Through the reaction of N-aminoethyl-3-aminopropyltriethoxysilane and intermediate microspheres A, N-aminoethyl-3-aminopropyltriethoxysilane can react with the hydroxyl groups to achieve the grafting of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite. The above reaction conditions can increase the reaction rate of N-aminoethyl-3-aminopropyltriethoxysilane and intermediate microspheres A, and increase the amount of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite, thereby synergistically improving the flame retardant, reinforcing, toxic gas adsorption and compactness improvement effects of the modified expandable graphite on the matrix.
[0045] If the weight of N-aminoethyl-3-aminopropyltriethoxysilane is too much, the amount of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite increases. Combined with the reactions of subsequent steps S30 and S40, too many molecular chains are introduced into the surface of expandable graphite, which weakens the bonding force between expandable graphites. The flame-retardant carbon layer still has cracks, and the flame-retardant and toxic gas barrier effects are reduced. If the weight of N-aminoethyl-3-aminopropyltriethoxysilane is too little, the modification effect of expandable graphite is reduced, and the flame-retardant, reinforcing, toxic gas adsorption and density improvement effects of the matrix are all reduced.
[0046] Optionally, in step S30, the weight ratio of monomer A, formaldehyde compound and intermediate microsphere B is (1-2): (1-3): 1;
[0047] The reaction temperature of step S30 is 50-60°C and the reaction time is 8-12h;
[0048] Preferably, the acidic catalyst is selected from at least one of nicotinic acid, sulfuric acid, acetic acid and nitric acid.
[0049] The above-mentioned weight ratio and reaction conditions can improve the reaction efficiency of monomer A, formaldehyde compounds and intermediate microspheres B, and promote monomer A and formaldehyde compounds to react with the amino groups in N-aminoethyl-3-aminopropyltriethoxysilane, thereby introducing new functional groups, increasing the number of functional groups in the intermediate microspheres B, and further synergistically improving the flame retardant and reinforcing effects of expandable graphite on the matrix.
[0050] Optionally, the monomer A is selected from diacetone acrylamide and benzylidene acetone;
[0051] The formaldehyde compound is selected from trioxymethylene and / or polyformaldehyde.
[0052] Optionally, the molar ratio of diacetone acrylamide to benzyl acetone is 3:1.
[0053] It has been verified that when a single type of monomer A reacts with formaldehyde compounds and intermediate microspheres B, after monomer A is connected to intermediate microspheres B, it will hinder the subsequent reaction of monomer A, thereby reducing the reaction participation rate of monomer A, resulting in a part of the molecular chain on the surface of the intermediate microsphere C being terminated with monomer A, and the other part being terminated with N-aminoethyl-3-aminopropyltriethoxysilane. The selection of diacetone acrylamide and benzylidene acetone with a molar ratio of 3:1 as monomer A can increase the reaction participation rate of monomer A, so that the reaction rate of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of intermediate microspheres B and monomer A is greater than 98%. In addition, two functional groups with amino groups and benzene rings can be simultaneously given to intermediate microspheres C, thereby enhancing the mechanical strength of the matrix and the chemical bonding with the matrix, thereby achieving a close and uniform connection between the modified expandable graphite and the matrix.
[0054] Optionally, in step S40, the weight ratio of the intermediate microspheres C to 3-mercaptopropyltriethoxysilane is 1:(5-10);
[0055] Preferably, the initiator in step S40 is a free radical initiator, the reaction temperature is 60-70° C., and the reaction time is at least 5 hours.
[0056] Preferably, the free radical initiator is AIBN.
[0057] The surface of the intermediate microsphere C is capped with monomer A, so that the surface of the intermediate microsphere contains a large number of double bonds. In step S40, the double bonds react with the thiol group to reintroduce the siloxane molecular chain into the modified expandable graphite. At this time, both ends of the molecular chain on the surface of the modified expandable graphite are siloxane molecular chains, which can improve the dispersibility and stability of the modified expandable graphite in the matrix. Under the premise of stable dispersion, the reaction uniformity of the amino group in the molecular chain on the surface of the modified expandable graphite and the isocyanate can be improved, thereby improving the uniformity of chemical bonding with the matrix, and the modified expandable graphite is uniformly embedded in the matrix. In a high temperature environment, the modified expandable graphite has a strong bonding force with the matrix, and the toxic matrix produced by the matrix is adsorbed and blocked at the first time, thereby improving the safety of the polyurethane thermal insulation material.
[0058] Optionally, the N series flame retardant is selected from at least one of ammonium polyphosphate, melamine, dicyandiamide, melamine cyanurate, and melamine borate.
[0059] Optionally, the isocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate;
[0060] The foaming agent is selected from at least one of n-pentane, n-hexane and cyclohexane;
[0061] The foam leveling agent is selected from silicone oil;
[0062] The first catalyst is selected from at least one of dibutyltin dilaurate, bis(dimethylaminoethyl) ether, N,N-dimethylcyclohexylamine, and 1,4-dimethylpiperazine.
[0063] According to another aspect of the present application, there is provided a method for preparing the high-efficiency flame-retardant thermal insulation material for construction as described in any one of the above items, comprising the following steps:
[0064] (1) mixing a modified polyol, an N-based flame retardant, modified expandable graphite, a condensed phase flame retardant, a foaming agent, a first catalyst, a foam leveling agent and water to obtain a first premix;
[0065] (2) adding 50% of isocyanate and diol to the first premix, and stirring to obtain a second premix;
[0066] (3) Add the remaining 50% of isocyanate to the second premix, stir and inject into a mold, and after foaming and curing, obtain a high-efficiency flame-retardant thermal insulation material for construction.
[0067] In step (1), the modified polyol, N-type flame retardant, modified expandable graphite, and condensed phase flame retardant are premixed, which can improve the compatibility between the above flame retardants and promote the uniform dispersion of the N-type flame retardant, modified expandable graphite, and condensed phase flame retardant. In step (2), the first premix is mixed with 50% of isocyanate and diol to form a polyurethane prepolymer. This step can preliminarily control the crosslinking degree of the polyurethane molecular chain, and the addition of diol promotes the further dispersion of the N-type flame retardant, so that a uniform polyurethane material can be formed in step (3).
[0068] Optionally, the foaming and curing temperature is 50-75°C.
[0069] The beneficial effects of this application include but are not limited to:
[0070] 1. The high-efficiency flame-retardant thermal insulation material for construction of the present application can achieve a flame-retardant effect of A2 level or above and has excellent thermal insulation performance. The mass proportion of inorganic materials in the material is low, and the overall density of the material is low. It is easier to use while ensuring mechanical strength and reduces the possibility of falling off.
[0071] 2. The high-efficiency flame-retardant thermal insulation material for construction of the present application can realize the main chain grafting of flame-retardant characteristic elements through modified polyols, thereby increasing the proportion of effective characteristic flame-retardant elements and making the flame-retardant characteristic elements evenly exert their flame-retardant effect.
[0072] 3. In the high-efficiency flame-retardant thermal insulation material for construction of the present application, the particle size of the modified expandable graphite and the condensed phase flame retardant is conducive to increasing the dispersion uniformity, while reducing the addition amount of the two substances, and the compatibility of the substance with the matrix is further improved through modification. DETAILED DESCRIPTION
[0073] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0074] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0075] Unless otherwise specified, the methods used in the embodiments of the present application are conventional methods in the prior art.
[0076] Example 1
[0077] This embodiment relates to the preparation of modified expandable graphite, which comprises the following steps:
[0078] S10: Phosphoric acid and urea are mixed in a molar ratio of (0.5-1):1, and reacted at 80-100° C. to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100° C. to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240° C. and 10-45 KPa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A;
[0079] S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups;
[0080] S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone;
[0081] S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.
[0082] Modified expandable graphites 1#-8# and comparative modified expandable graphites D1#-D4# were prepared according to the above preparation steps, as follows:
[0083] Modified expandable graphite 1#
[0084] The preparation method of the modified expandable graphite 1# comprises the following steps:
[0085] S10: Phosphoric acid and urea are mixed at a molar ratio of 0.5:1, and reacted at 100°C to obtain urea phosphate, expandable graphite, dispersant, and emulsifier are added to the urea phosphate, wherein the expandable graphite accounts for 5% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate, and the stirring is continued at 100°C to obtain a colloid, the colloid is placed in an emulsifier for emulsification, and then transferred to a polymerization furnace for polymerization at 240°C and 10Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A, and the particle size of the intermediate microspheres A is 0.5μm;
[0086] S20: Mixing intermediate microspheres A and N-aminoethyl-3-aminopropyltriethoxysilane in a weight ratio of 1:1 in N,N-dimethylformamide and heating to 80°C, reacting for 10 hours under nitrogen protection, filtering, washing, and drying to obtain intermediate microspheres B with amino groups;
[0087] S30: para-acetoxystyrene, trioxymethylene and intermediate microspheres B in a weight ratio of 1:1:1 are mixed in methanol, 37% concentrated hydrochloric acid is slowly added dropwise, and the amount of concentrated hydrochloric acid added is 30% of the weight of the intermediate microspheres B, and then reacted at 50° C. under nitrogen protection for 12 hours, and the reaction solution is neutralized to neutrality with sodium bicarbonate, and filtered, washed, and dried to obtain intermediate microspheres C;
[0088] S40: The intermediate microspheres C with a weight ratio of 1:5 are placed in a solution of 3-mercaptopropyltriethoxysilane, and the solvent is a mixed solvent of ethanol and water with a volume ratio of 5:1. Then, AIBN accounting for 1% of the weight of the intermediate microspheres is added, and after reacting at 70°C under nitrogen protection for 5 hours, the modified expandable graphite 1# is obtained by suction filtration, washing and drying.
[0089] Modified expandable graphite 2#
[0090] The preparation method of the modified expandable graphite 2# comprises the following steps:
[0091] S10: Phosphoric acid and urea are mixed at a molar ratio of 1:1, and reacted at 80°C to obtain urea phosphate, expandable graphite, dispersant, and emulsifier are added to the urea phosphate, wherein the expandable graphite accounts for 30% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate, and the stirring is continued at 80°C to obtain a colloid, the colloid is placed in an emulsifier for emulsification, and then transferred to a polymerization furnace for polymerization at 150°C and 45Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A, and the particle size of the intermediate microspheres A is 10μm;
[0092] S20: Mix the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a weight ratio of 1:2 in N,N-dimethylformamide and heat to 80°C. React for 8 hours under nitrogen protection. Filter, wash and dry to obtain the intermediate microsphere B with amino groups. The reaction equation is as follows:
[0093]
[0094] S30: Monomer A, trioxymethylene and intermediate microspheres B in a weight ratio of 2:3:1 are mixed in methanol, 37% concentrated hydrochloric acid is slowly added dropwise, and the amount of concentrated hydrochloric acid added is 30% of the weight of the intermediate microspheres B. Then, the reaction is carried out at 60°C under nitrogen protection for 8 hours, and the reaction solution is neutralized to neutrality with sodium bicarbonate, filtered, washed and dried to obtain intermediate microspheres C. Monomer A is selected from diacetone acrylamide and benzylidene acetone in a molar ratio of 3:1, and the reaction equation is as follows:
[0095]
[0096] Wherein R represents monomer A, and both amino groups in the intermediate microsphere B in this step can participate in the reaction, thereby obtaining two compounds of the structure of Formula 1 and the structure of Formula 2, and the compound of the structure of Formula 1 accounts for more than 70% in the above reaction;
[0097] S40: placing the intermediate microspheres C with a weight ratio of 1:10 in a solution of 3-mercaptopropyltriethoxysilane, wherein the solvent is a mixed solvent of ethanol and water with a volume ratio of 5:1, and then adding AIBN accounting for 1% of the weight of the intermediate microspheres. After reacting at 60°C under nitrogen protection for 8 hours, filtering, washing and drying are performed to obtain modified expandable graphite 2#. In this step, the carbon-carbon double bond in the monomer A undergoes an addition reaction with 3-mercaptopropyltriethoxysilane.
[0098] Modified expandable graphite 3#
[0099] The difference between the modified expandable graphite 3# and the modified expandable graphite 2# is that in step S10, the expandable graphite accounts for 40% of the weight of the urea phosphate, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0100] Modified expandable graphite 4#
[0101] The difference between the modified expandable graphite 4# and the modified expandable graphite 2# is that in step S20, the weight ratio of the intermediate microspheres A and N-aminoethyl-3-aminopropyltriethoxysilane is 1:0.5, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0102] Modified expandable graphite 5#
[0103] The difference between the modified expandable graphite 5# and the modified expandable graphite 2# is that the weight ratio of the monomer A, the formaldehyde compound and the intermediate microspheres B in step S30 is 0.8:3:1, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0104] Modified expandable graphite 6#
[0105] The difference between the modified expandable graphite 6# and the modified expandable graphite 2# is that in step S30, the monomer A is selected from diacetone acrylamide and benzyl acetone in a molar ratio of 1:3, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0106] Modified expandable graphite 7#
[0107] The difference between the modified expandable graphite 7# and the modified expandable graphite 2# is that in step S40, the weight ratio of the intermediate microspheres C to 3-mercaptopropyltriethoxysilane is 1:3, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0108] Modified expandable graphite 8#
[0109] The difference between the modified expandable graphite 8# and the modified expandable graphite 2# is that the particle size of the intermediate microsphere A is 15 μm, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0110] Comparison of modified expandable graphite D1#
[0111] The difference between the comparative modified expandable graphite D1# and the modified expandable graphite 2# is that step S10 is not performed, and in step S20, the expandable graphite with a weight ratio of 1:2 is directly reacted with N-aminoethyl-3-aminopropyltriethoxysilane, the particle size of the expandable graphite is 10 μm, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0112] Comparison of modified expandable graphite D2#
[0113] The difference between the comparative modified expandable graphite D2# and the modified expandable graphite 2# is that steps S20-S40 are not performed, the intermediate microspheres A are the final modified expandable graphite, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0114] Comparison of modified expandable graphite D3#
[0115] The difference between the comparative modified expandable graphite D3# and the modified expandable graphite 2# is that step S40 is not performed, the intermediate microspheres C are the final modified expandable graphite, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0116] Comparison of modified expandable graphite D4#
[0117] The difference between the comparative modified expandable graphite D4# and the modified expandable graphite 2# is that 3-aminopropyltriethoxysilane is used instead of N-aminoethyl-3-aminopropyltriethoxysilane in step S20, and the remaining steps are the same as those of the modified expandable graphite 2#.
[0118] Test Example 1
[0119] The modified expandable graphite prepared above was subjected to a gas adsorption test. The test results are shown in Table 1. The test method is as follows:
[0120] Experimental group: 1g of modified expandable graphite was placed in the non-combustible plate of the reactor, and a polyurethane sheet (5cm long * 5cm wide * 1cm thick) without adding flame retardant was fixed and hung in the reactor. Oxygen (100ml / min) was introduced into the reactor, and the polyurethane sheet was ignited and burned with an ignition device until it was completely burned. The concentrations of HCN, CO2, CO, NO, and NO2 in the reactor were tested.
[0121] Blank group: A polyurethane sheet of the same material and size was fixed and hung in the reactor. Nothing was placed in the non-combustible sheet. After the combustion was completed, the concentrations of HCN, CO2, CO, NO, and NO2 in the reactor were recorded.
[0122] The polyurethane sheets of the experimental group and the blank group were prepared by placing polyether polyol, foam leveler, catalyst, blowing agent and water in a weight ratio of 75:2.7:1.5:1.5:1 in a container, mixing and stirring with a high-speed stirrer for 2 minutes to obtain a uniform mixed liquid, and then adding PAPI and stirring at a high speed for 20 seconds to obtain a mixture. The weight ratio of PAPI to water was 100:1. The mixture was quickly added to the mold for foaming, and the closed mold temperature was controlled at 65°C for 30 minutes for aging. After the foaming was completed, the mold was opened and cut into 5 cm long * 5 cm wide * 1 cm thick pieces.
[0123] The modified expandable graphite prepared in Example 1 was subjected to experimental group tests in turn, and the adsorption rates of various gases were calculated based on the comparison of the tested gas concentrations with the blank group. The calculation method is as follows:
[0124] HCN adsorption rate = (HCN concentration in blank group - HCN concentration in experimental group) / HCN concentration in blank group * 100;
[0125] CO2 adsorption rate = (CO2 concentration of blank group - CO2 concentration of experimental group) / CO2 concentration of blank group * 100;
[0126] CO adsorption rate = (CO concentration of blank group - CO concentration of experimental group) / CO concentration of blank group * 100;
[0127] NO adsorption rate = (NO concentration in blank group - NO concentration in experimental group) / NO concentration in blank group * 100;
[0128] NO2 adsorption rate = (NO2 concentration in blank group - NO2 concentration in experimental group) / NO2 concentration in blank group * 100.
[0129] Table 1
[0130]
[0131]
[0132] According to the data in Table 1, the modified expandable graphite can adsorb HCN, CO2, CO, NO, and NO2. Therefore, when it is used in polyurethane sheets, it can adsorb and block the toxic gases produced in the early stage of combustion and reduce the combustion hazards.
[0133] Example 2
[0134] This embodiment relates to a high-efficiency flame-retardant heat-insulating material for construction and a preparation method thereof. The high-efficiency flame-retardant heat-insulating material for construction, measured by weight, comprises:
[0135] 110-120 parts of modified polyol, 8-10 parts of diol, 120-140 parts of isocyanate, 10-20 parts of N-series flame retardant, 5-20 parts of modified expandable graphite, 150-280 parts of condensed phase flame retardant, 13-15 parts of foaming agent, 0.3-0.5 parts of first catalyst, 2.5-3.0 parts of uniform foaming agent and 1 part of water, wherein the modified polyol contains phosphorus element.
[0136] The preparation of the high-efficiency flame-retardant heat-insulating material for building comprises the following steps:
[0137] (1) mixing a modified polyol, an N-based flame retardant, modified expandable graphite, a condensed phase flame retardant, a foaming agent, a first catalyst, a foam leveling agent and water to obtain a first premix;
[0138] (2) adding 50% of isocyanate and diol to the first premix, and stirring to obtain a second premix;
[0139] (3) Add the remaining 50% of isocyanate to the second premix, stir and inject into a mold, and after foaming and curing, obtain a high-efficiency flame-retardant thermal insulation material for construction.
[0140] Materials 1#-8# and comparative materials D1#-D3# were prepared according to the above preparation method. The specific preparation method is as follows:
[0141] Material 1#
[0142] Preparation of modified polyols: After mixing polyols and tributyl phosphate in a weight ratio of 8:1, add dibutyltin oxide accounting for 0.5% of the weight of the polyol and react at 120°C for 15 hours, adjust the pH to 7 with 1 mol / L sodium hydroxide solution, and obtain modified polyols by reduced pressure distillation and suction filtration. The polyols used are polyether triol and polycarbonate polyol in a weight ratio of 1:1, and the hydroxyl values of the polyether triol and the polycarbonate polyol are both 650 mg KOH / g.
[0143] Preparation of diols:
[0144] S1: N, N-bis (hydroxymethyl) -urea was dissolved in a mixed solvent of water and ethanol in a weight ratio of 2: 1, and 85% formic acid solution and 37% formaldehyde solution were added at room temperature, and the molar ratio of N, N-bis (hydroxymethyl) -urea, formaldehyde and formaldehyde was 1: 1: 1, and then the temperature was raised to 80 ° C for 9 hours, and then the pH was adjusted to 10 with 10% NaOH solution, and the intermediate was obtained after ether extraction and drying;
[0145] S2: The intermediate was dissolved in ethanol, 2% of citric acid and 5% of disodium ethylenediaminetetraacetate by weight of N,N-bis(hydroxymethyl)urea were added, the temperature was raised to 60°C, 30% hydrogen peroxide was added, the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)urea was 1:1, the reaction was continued for 6 hours, the product was distilled and purified by silica gel column chromatography (the eluent was ethyl acetate: petroleum ether = 1:10) to obtain a diol.
[0146] Preparation of modified expandable graphite:
[0147] Expandable graphite with a particle size of 0.5 μm was placed in a vinyl tri(β-methoxyethoxy) silane solution, the weight ratio of expandable graphite to vinyl tri(β-methoxyethoxy) silane was 10:1, stirred at 60° C. for 3 h, then centrifuged and dried to obtain modified expandable graphite.
[0148] The preparation of material 1# includes the following steps:
[0149] (1) 110 parts of modified polyol, 20 parts of ammonium polyphosphate, 5 parts of modified expandable graphite, 75 parts of calcium silicate, 75 parts of chromium hydroxide, 13 parts of n-hexane, 0.3 parts of dibutyltin dilaurate, 2.5 parts of silicone oil and 1 part of water were stirred and mixed for 2 minutes to obtain a first premix, wherein the average particle size of calcium silicate and chromium hydroxide was 9.5 μm;
[0150] (2) adding 60 parts of toluene diisocyanate and 8 parts of diol to the first premix, stirring evenly to obtain a second premix;
[0151] (3) Add 60 parts of toluene diisocyanate to the second premix, stir for 20 seconds, inject into a mold, foam and cure at 50° C. for 30 minutes, and open the mold to obtain material 1#.
[0152] Material 2#
[0153] Preparation of modified polyols:
[0154] After mixing a polyol and dimethyl methylphosphonate in a weight ratio of 9:1, adding dibutyltin oxide accounting for 0.5% of the weight of the polyol, reacting at 150°C for 12 hours, adjusting the pH to 7 with a 1 mol / L sodium hydroxide solution, and obtaining a modified polyol by reduced pressure distillation and suction filtration, wherein the polyol used is a polyether triol and a polyacrylate polyol in a weight ratio of 1:1, and the hydroxyl values of the polyether triol and the polyacrylate polyol are both 400 mg KOH / g.
[0155] Preparation of diols:
[0156] S1: N, N-bis (hydroxymethyl) -urea was dissolved in a mixed solvent of water and ethanol in a weight ratio of 3:1, and 85% formic acid solution and 37% formaldehyde solution were added at room temperature, and the molar ratio of N, N-bis (hydroxymethyl) -urea, formaldehyde and formaldehyde was 1:1:1, and then the temperature was raised to 70 ° C for 12 hours, and then the pH was adjusted to 11 with 10% NaOH solution, and the intermediate was obtained after ether extraction and drying;
[0157] S2: The intermediate was dissolved in ethanol, 2% of citric acid based on the weight of N,N-bis(hydroxymethyl)urea and 5% of disodium ethylenediaminetetraacetate based on the weight of N,N-bis(hydroxymethyl)urea were added, the temperature was raised to 70°C, 30% hydrogen peroxide was added, the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)urea was 1:1, the reaction was continued for 4 hours, the product was distilled and purified by silica gel column chromatography (the eluent was ethyl acetate: petroleum ether = 1:10) to obtain a diol.
[0158] Preparation of modified expandable graphite:
[0159] Expandable graphite with a particle size of 10 μm was placed in a 3-aminopropyltriethoxysilane solution, the weight ratio of expandable graphite to 3-aminopropyltriethoxysilane was 10:1, stirred at 60° C. for 3 h, then centrifuged and dried to obtain modified expandable graphite.
[0160] The preparation of material 2# includes the following steps:
[0161] (1) 120 parts of modified polyol, 10 parts of melamine, 20 parts of modified expandable graphite, 140 parts of silicon oxide, 140 parts of aluminum oxide, 15 parts of n-pentane, 0.5 parts of dibutyltin dilaurate, 3.0 parts of silicone oil and 1 part of water were stirred and mixed for 2 minutes to obtain a first premix, wherein the particle size of silicon oxide and aluminum oxide were both 8 μm;
[0162] (2) adding 70 parts of isophorone diisocyanate and 10 parts of diol to the first premix, and stirring to obtain a second premix;
[0163] (3) Add 70 parts of isophorone diisocyanate to the second premix, stir for 20 seconds, inject into a mold, foam and cure at 75° C. for 30 minutes, and open the mold to obtain material 2#.
[0164] Material 3#
[0165] The difference between material 3# and material 2# is that dimethyl methylphosphonate and tris(β-chloroethyl) phosphate in a weight ratio of 1:4 are used to replace dimethyl methylphosphonate in the preparation of the modified polyol, and the rest is the same as material 2#, namely material 3#.
[0166] Material 4#
[0167] The difference between material 4# and material 2# is that 1,4-butanediol is used as the diol, and the rest is the same as material 2#, that is, material 4# is obtained.
[0168] Material 5#
[0169] The difference between material 5# and material 2# is that N,N-bis(hydroxymethyl)urea is used as diol, and the rest is the same as material 2#, namely material 5#.
[0170] Material 6#
[0171] The difference between the present material 6# and the material 2# is that the modified expandable graphite 2# of Example 1 is used as the modified expandable graphite, and the rest is the same as the material 2#, that is, the material 6# is obtained.
[0172] Material 7#
[0173] The difference between the present material 7# and the material 2# is that the comparative modified expandable graphite D1# of Example 1 is used as the modified expandable graphite, and the rest is the same as the material 2#, that is, the material 7# is obtained.
[0174] Material 8#
[0175] The difference between the present material 8# and the material 2# is that the comparative modified expandable graphite D2# of Example 1 is used as the modified expandable graphite, and the rest is the same as the material 2#, that is, the material 8# is obtained.
[0176] Comparative material D1#
[0177] The difference between the comparative material D1# and the material 2# is that the polyether triol and the polyacrylate polyol are directly used in a weight ratio of 1:1, and the polyol is not modified. The rest is the same as the material 2#, that is, the comparative material D1# is obtained.
[0178] Comparative material D2#
[0179] The difference between the comparative material D2# and the material 2# is that the N-series flame retardant melamine is not added, and the rest is the same as the material 2#, that is, the comparative material D2# is obtained.
[0180] Comparative material D3#
[0181] The difference between the comparative material D3# and the material 2# is that the condensed phase flame retardants silicon oxide and aluminum oxide are not added, and the rest is the same as the material 2#, that is, the comparative material D3# is obtained.
[0182] Test Example 2
[0183] The density, thermal conductivity, flame retardancy and mechanical properties of the material prepared in Example 2 above were tested, and the results are shown in Table 2 below.
[0184] Table 2
[0185]
[0186] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A high-efficiency flame-retardant heat-insulating material for construction, characterized in that: By weight, it includes: 110-120 parts of modified polyol, 8-10 parts of diol, 120-140 parts of isocyanate, 10-20 parts of N-series flame retardant, 5-20 parts of modified expandable graphite, 150-280 parts of condensed phase flame retardant, 13-15 parts of blowing agent, 0.3-0.5 parts of first catalyst, 2.5-3.0 parts of uniform foaming agent, 1 part of water; The modified polyol contains phosphorus; The modification method of the modified expandable graphite is: S10: Phosphoric acid and urea are mixed at a molar ratio of (0.5-1):1, and reacted at 80-100°C to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100°C to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240°C and 10-45Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A; S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups; S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone; S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.
2. The high-efficiency flame-retardant heat-insulating material for construction according to claim 1, characterized in that: The modified polyol is obtained by modifying the polyol with a liquid phosphorus-based flame retardant, and the specific preparation method is as follows: After mixing the polyol and the liquid phosphorus flame retardant in a weight ratio of 8-9:1, adding a second catalyst and reacting at 120-150° C. for 12-15 hours to obtain a modified polyol.
3. The high-efficiency flame-retardant heat-insulating material for construction according to claim 2, characterized in that: The liquid phosphorus-based flame retardant is selected from at least one of dimethyl methylphosphonate, triphenyl phosphite, tributyl phosphate, and tris(β-chloroethyl) phosphate.
4. The high-efficiency flame-retardant heat-insulating material for construction according to claim 3, characterized in that: The liquid phosphorus-based flame retardant is selected from dimethyl methylphosphonate and tris(β-chloroethyl) phosphate in a weight ratio of 1:
4.
5. The high-efficiency flame-retardant heat-insulating material for construction according to claim 1, characterized in that: The diol is prepared from N,N-bis(hydroxymethyl)-urea, and the specific preparation method is as follows: S1: dissolving N,N-bis(hydroxymethyl)-urea in a solvent, adding formic acid and formaldehyde at room temperature, wherein the molar ratio of N,N-bis(hydroxymethyl)-urea, formic acid and formaldehyde is 1:1:1, then heating to 70-80°C for reaction for 9-12h, then adjusting the pH to 10-11, extracting and drying to obtain an intermediate; S2: dissolving the intermediate in ethanol, adding a small amount of citric acid and disodium ethylenediaminetetraacetate, heating to 60-70°C, adding hydrogen peroxide, wherein the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)-urea is 1:1, reacting for at least 4 hours, distilling and purifying to obtain the diol.
6. The high-efficiency flame-retardant heat-insulating material for construction according to claim 5, characterized in that: The added amount of the citric acid accounts for 2% of the weight of N,N-bis(hydroxymethyl)-urea, and the added amount of the disodium ethylenediaminetetraacetate accounts for 5% of the weight of N,N-bis(hydroxymethyl)-urea.
7. The high-efficiency flame-retardant heat-insulating material for construction according to claim 1, characterized in that: The condensed phase flame retardant is selected from at least one of Sb2O3, Mg(OH)2, Al(OH)3, B2O6Zn3, silicon oxide, aluminum oxide, aluminum silicate, calcium silicate, clay powder, feldspar powder, talcum powder, copper oxide, copper hydroxide, cobalt hydroxide, chromium hydroxide, and zinc hydroxide.
8. The high-efficiency flame-retardant heat-insulating material for construction according to claim 1, characterized in that: The particle size of the condensed phase flame retardant is less than 10 μm; The particle size of the modified expandable graphite is 0.5-10 μm.
9. The high-efficiency flame-retardant heat-insulating material for construction according to claim 1, characterized in that: The N series flame retardant is selected from at least one of ammonium polyphosphate, melamine, dicyandiamide, melamine cyanurate salt, and melamine borate.
10. The method for preparing a high-efficiency flame-retardant heat-insulating material for construction according to any one of claims 1 to 9, characterized in that: The steps include: (1) mixing a modified polyol, an N-based flame retardant, modified expandable graphite, a condensed phase flame retardant, a foaming agent, a first catalyst, a uniform foaming agent and water to obtain a first premix; (2) adding 50% of isocyanate and diol to the first premix, and stirring to obtain a second premix; (3) Add the remaining 50% of isocyanate to the second premix, stir and inject into a mold, and after foaming and curing, obtain a high-efficiency flame-retardant thermal insulation material for construction.
Citation Information
Patent Citations
Core-shell synergistic flame retardant polyurethane microencapsulation expandable graphite and application thereof in rigid polyurethane foaming plastic
CN103554428A
Polyurethane plastic runway easy to clean and maintain and preparation method thereof
CN106589303A